A policy-theoretic analysis of sample survey of the Mi’maq people of Cape Breton in the light of the knowledge-based world view - Choudhury, Masudul Alam; Mohd. Nor, Hanapi (MCB UP Limited, 1997)
Carries out a statistical and economic analysis of socio-economic survey results on the Mi'kmaq People of Cape Breton in the light of the criterion of the social wellbeing function. Focuses on studying the social wellbeing criterion with the socio-economic variables involved in the surveys in a relational perspective among alternatives. Points out that this approach is distinct from the neoclassical resource substitution method. Instead, the relational perspective is shown to be premissed on a system of universal complementarities.